2016
DOI: 10.11138/ccmbm/2016.13.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid in the management of osteoarthritis: injection therapies innovations

Abstract: SummaryOsteoarthritis (OA) is a chronic degenerative joint disease characterized by pain and progressive functional limitation. Viscosupplementation with intra-articular (IA) hyaluronic acid (HA) could be a treatment option in OA, however recommendations made in different international guidelines for the non-surgical management of OA are not always concordant with regard to the role of IA injection therapies. Results from a recent Italian Consensus Conference underline how IA-HA to treat OA represents a widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In general, patients below 65 years of age and those with less severe OA are likely to be benefited from HA viscosupplementation (252). Also, some clinical studies indicated that therapy with an IA HA formulation with a higher-MW (e.g., hylan G-F 20) was more effective in relieving OA-associated pain than therapies with lower-MWs (e.g., sodium hyaluronate) (142, 253255).…”
Section: Pharmacotherapeutics Of Hamentioning
confidence: 99%
“…In general, patients below 65 years of age and those with less severe OA are likely to be benefited from HA viscosupplementation (252). Also, some clinical studies indicated that therapy with an IA HA formulation with a higher-MW (e.g., hylan G-F 20) was more effective in relieving OA-associated pain than therapies with lower-MWs (e.g., sodium hyaluronate) (142, 253255).…”
Section: Pharmacotherapeutics Of Hamentioning
confidence: 99%
“…There is no evidence in the available publications that a particular type of HA is superior to others. However, some clinical studies show that preparations with a higher MW were more effective than those with a lower MW in relieving pain associated with OA [27,28]. Intra-articular application of HA increases the quality of synovial fluid by increasing its viscoelastic properties.…”
Section: Review and Disscusionmentioning
confidence: 99%
“…HA-CD44 interaction is essential for the normal homeostasis of the cartilage [16,17], since it can modulate cartilage metabolism and promote matrix remodeling of the cartilage [18,19]. There is an ongoing database on the effects of HA in OA, in a review on the subject, Rutjes et al [20] concluded that there is a small and clinically irrelevant benefit while Santilli et al [21] and Maheu et al [22] concluded that intra-articular injection of HA results in longlasting improvements in function, including the potential to avoid a joint prosthetic implant and pain reduction. Additionally, repeated intra-articular injections of HA have been shown to relief pain and improve joint function with the effects persisting for up to 26 weeks [23].…”
Section: Introductionmentioning
confidence: 99%